Distribution Patterns of Three Molecularly Defined Classes of GABAergic Neurons Across Columnar Compartments in Mouse Barrel Cortex - Almási, Zsuzsanna; Dávid, Csaba; Witte, Mirko; Staiger, Jochen F. (Frontiers in Neuroanatomy, 2019)
The mouse somatosensory cortex is an excellent model to study the structural basis of cortical information processing, since it possesses anatomically recognizable domains that receive different thalamic inputs, which indicates spatial segregation of different processing tasks. In this work we examined three genetically labeled, non-overlapping subpopulations of GABAergic neurons: parvalbumin- (PV+), somatostatin- (SST+) and vasoactive intestinal polypeptide-expressing (VIP+) cells. Each of these subpopulations displayed a unique cellular distribution pattern across layers. In terms of columnar localization, the distribution of these three populations was not quantitatively different between barrel-related versus septal compartments in most layers. However, in layer IV, SST+ and VIP+, but not PV+ neurons preferred the septal compartment over barrels. The examined cell types showed a tendency toward differential distribution in supragranular and infragranular barrel-related versus septal compartments, too. Our data suggests that the location of GABAergic neuron cell bodies correlates with the spatial pattern of cortical domains receiving different kinds of thalamic input. Thus, at least in layer IV, lemniscal inputs present a close spatial relation preferentially to PV+ cells whereas paralemniscal inputs target compartments in which more SST+ and VIP+ cells are localized. Our findings suggest pathway-specific roles for neocortical GABAergic neurons.